2023
DOI: 10.1111/disa.12592
|View full text |Cite
|
Sign up to set email alerts
|

Defining, collecting, and sharing perishable disaster data

Abstract: Researchers across disciplines have long sought to collect ‘perishable data’ in the context of disasters. Yet, this data type is neither consistently defined nor discussed in specific detail in the literature. To address this gap, this paper defines perishable data and provides guidance on ways to improve both how it is collected and shared. Here, perishable data is conceptualised as highly transient data that may degrade in quality, be irrevocably altered, or be permanently lost if not gathered soon after it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Early on in the pandemic, the research team identified the importance of collecting perishable data to document the challenges dealt with by agritourism operators. Perishable data refers to transient data that may decay in quality or be permanently altered or lost if not captured shortly after it is produced [22]. Agritourism operations may employ temporary practices and strategies to adapt to changing agricultural markets, public preferences, and tourism seasonality [23], which is a characteristic of perishable data.…”
Section: Background and Sampling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Early on in the pandemic, the research team identified the importance of collecting perishable data to document the challenges dealt with by agritourism operators. Perishable data refers to transient data that may decay in quality or be permanently altered or lost if not captured shortly after it is produced [22]. Agritourism operations may employ temporary practices and strategies to adapt to changing agricultural markets, public preferences, and tourism seasonality [23], which is a characteristic of perishable data.…”
Section: Background and Sampling Proceduresmentioning
confidence: 99%
“…Agritourism operations may employ temporary practices and strategies to adapt to changing agricultural markets, public preferences, and tourism seasonality [23], which is a characteristic of perishable data. Capturing perishable data as early as possible has helped governmental agencies and humanitarian organizations to capture the immediate impacts of crisis or disasters and prioritize and adapt efforts to effectively address future planning and response [22]. Given the ongoing and constantly changing impacts of the COVID-19 crisis, the capture of this data during the early days of the pandemic proved crucial.…”
Section: Background and Sampling Proceduresmentioning
confidence: 99%